Mathematical Modeling and Experimental Evaluation of the Stress in the Connecting Elements of the Rods at a Rotational-Impact Loading - Saruev L. A. Lev Alekseevich (Designing and Modelling of Machines and Mechanisms, 2015)
Title screen